Peran Manajemen Efektivitas E-commerce Shopee Di Masa Pandemi Covid-19 - Pusponegoro, Marvellda; Tjahyadi, Rully Arlan (Universitas Muhammadiyah Surakarta, 2023)
The Covid-19 pandemic has led to an increase in the use of e-commerce platforms. Along with the effectiveness of the Shopee e-commerce platform and the economic benefits it provides, customers have shifted to shopping through Shopee during the Covid-19 pandemic. This study aims to empirically examine the role of Shopee e-commerce management effectiveness during the pandemic. The researcher used an explanatory research method to explain the influence between the dependent and independent variables in the hypothesis. Sampling was done using purposive sampling technique, resulting in 200 respondents. Each proposed hypothesis in this study was tested using descriptive statistical analysis, classical assumption tests, path analysis, and hypothesis testing through the SPSS statistical analysis application. The research results show that the effectiveness of the e-commerce platform has an influence on economic benefits, economic benefits have an influence on sustainable consumption, and the effectiveness of the e-commerce platform has an influence on sustainable consumption mediated by economic benefits. From these tests, it can be concluded that the shopping interest of the community, both before and after the pandemic, is influenced by the effectiveness of the e-commerce platform, characterized by repeated purchasing behavior of the community after considering the economic benefits and credibility provided by the Shopee e-commerce platform.